Fibroblasts from HPV-negative oropharynx squamous cell carcinomas stimulate the release of osteopontin from cancer cells via the release of IL-6 - Hendawi, Naeima Yahia; Crane, Hannah L.; Mehanna, Hisham; Bolt, Robert; Lambert, Daniel W.; Hunter, Keith D. (Frontiers in Oral Health, 2024)
Introduction: HPV-associated oropharyngeal squamous cell carcinoma (OPSCC) shows distinct biological and clinical behaviour when compared to HPV-negative OPSCC. The overall role of the tumour microenvironment (TME) in head and neck cancer progression and metastasis has been studied intensively, but differences in HPV-negative and HPV-positive OPSCCs are less understood. Objective: To investigate the role of cancer-associated fibroblasts (CAFs) and the functional interactions of normal tonsil fibroblasts (NTFs) and OP CAFs with HPV+ and HPV- OPSCC cells and explore novel candidates in tumour-fibroblast crosstalk. Materials and methods: A retrospective cohort of 143 primary OPSCCs was characterised using HPV16/18 RNAScope assay, p16 IHC and ɑ-SMA. Four OPSCC, three NTF and 2 new OPSCC CAF cultures were used to assess the cytokine-based interactions using cytokine arrays on conditioned media (CM), followed by co-culture approaches to identify the role of individual cell types and the role of OPN (SPP1) and IL-6 in SCC/fibroblast communication. Results: HPV status was associated with better overall survival. Although ɑ-SMA expression was observed in both OPSCC subtypes, it provided survival stratification only in the HPV-positive group (Log-Rank p=0.02). Three normal tonsillar fibroblast cultures (NTFs) were characterised by induction of myofibroblastic and senescent phenotypes with similar reactivity to our published NOF phenotype. The OPSCC-derived CAF cultures were characterised and their baseline myofibroblastic and senescence phenotypes varied. Cytokine array analysis of CM to identify novel candidates in the crosstalk between OPSCC tumour cells and NTFs/CAFs identified differences in the cytokine profiles on comparison of HPV+ and HPV- OPSCC cells. Osteopontin (OPN/SPP1) was identified, particularly in HPV-negative OPSCC cell analyses. We have demonstrated that OPN was produced by the OPSCC cells and revealed an associated upregulation of IL-6 in fibroblasts. Treatment of NTFs with rOPN showed alteration in phenotype, including increased contraction and IL-6 production. Antibody-mediated inhibition of CD44v6 attenuated the production of IL-6 by OPN in NTFs. Conclusion: This investigation with OPSCC fibroblasts provides novel insights into the role of CAFs in OPSCC mediated by IL-6 stimulated release of OPN from HPV negative OPSCC cells. The details of HPV-positive SCC cell/fibroblast cytokine crosstalk remain elusive.